1990
DOI: 10.1128/jcm.28.6.1249-1253.1990
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay for immunoglobulin M specific antibody for the diagnosis of melioidosis

Abstract: Indirect hemagglutination (IHA) is commonly used for serodiagnosis of melioidosis. However, in endemic areas, high background titers in normal populations and occasional low titers in patients with septicemic melioidosis prompted a search for a more sensitive and more specific method of serodiagnosis. An indirect fluorescent-antibody test for immunoglobulin M (IgM) specific antibody to Pseudomonas pseudomallei was more sensitive and more specific, but fluorescence microscopes are rarely available in the endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…As shown in our control from an endemic area (Table 2), subclinical infection forced the increase of the cutoff value with a subsequent decrease in sensitivity. To compensate for the loss of sensitivity and to cover both chronic and acute cases, parallel combination of the tests have been proposed (6). IHA which measured total antibody showed better agreement with the protein A gold blot which reacted preferably with IgG (3).…”
mentioning
confidence: 99%
“…As shown in our control from an endemic area (Table 2), subclinical infection forced the increase of the cutoff value with a subsequent decrease in sensitivity. To compensate for the loss of sensitivity and to cover both chronic and acute cases, parallel combination of the tests have been proposed (6). IHA which measured total antibody showed better agreement with the protein A gold blot which reacted preferably with IgG (3).…”
mentioning
confidence: 99%
“…The IHA test is widely used for the serodiagnosis of melioidosis because of its simplicity and low cost. The usefulness of IHA test was compared with that of IgM-ELISA [2,6,15], IgM gold blot [16] and IFA [4] tests. These studies concluded that IHA should not be used alone in the diagnosis of melioidosis, especially in the endelmic areas of melioidosis.…”
Section: Discussionmentioning
confidence: 99%
“…A partially purified protein antigen (19.5 kDa) was reported to be highly sensitive and specific for the diagnosis of melioidosis [3], however, due to its protein nature, the stability has not been guaranteed and satisfactory techniques for the preparation of this antigen make it difficult for use in most endemic areas. In comparison with IHA, the ELISA generally gives higher sensitivity and specificity, however, in some melioidosis patients, ELISA shows negative results in IHA-positive sera [2]. The combined results of IHA and ELISA tests, therefore, may be more reliable in the diagnosis of melioidosis than either test alone.…”
Section: Melioidosis Is An Infectious Disease Caused Bymentioning
confidence: 98%
See 2 more Smart Citations